Women primary school principals in Cyprus: barriers and facilitators to progression - Karamanidou, Maria; Bush, Tony (Commonwealth Council for Educational Administration and Management, 2017)
This paper examines the career progress of female principals in Cypriot primary schools in accessing leadership. It reports part of a mixed methods study focused on the extent to which women primary school principals in Cyprus face barriers during their accession and enactment, and what these are. The study was exploratory, and used both a survey and interviews. The data were collected sequentially, with the survey preceding the interviews. The findings show that family influences, stereotyping, previous educational experience, training seminars, Cypriot society and culture, lack of female role models, and discrimination were powerful influences on the career trajectory of these women primary school principals. These themes recur in several places, showing the pervasive nature of these influences on women principals in Cyprus. Many of these findings resonate with insights from previous research.